Succinate-Dehydrogenase and Glucose-6-Phosphate Dehydrogenase Activities of Human Sperm at Low Temperature Preservation Stages - Rodionova, V. L.; Nikitchenko, Yu. V.; Tchoob, N. N.; Cherepanov, V. V. (Problems of Cryobiology and Cryomedicine, 2006)
We have carried out the research in glucose-6-phosphatedehydrogenase (G6PDG) and succinate dehydrogenase (SDG) activities in human sperm following the incubation with cryoprotective medium (glycerol-lactose-yolk) and after hypothermic storage and freezing down to liquid nitrogen temperature. At the low temperature steps preservation the activities were characterized with slight differences at selected cooling regimens. Statistically significant variation in SDG and G6PDG activities was demonstrated during samples’ storage at –12°C both with and without cryoprotective medium.